Characterization and Plasmid Profile of Resistant Klebsiella pneumoniae Isolates in Patients with Urinary Tract Infection in Nasarawa State, Nigeria - Orole, Olukayode Olugbenga; Hadi, Naja’atu Shehu (International Journal of Applied Sciences and Biotechnology, 2020)
Klebsiella pneumoniae has been identified as an urgent threat to human health based on its increasing antimicrobial resistance to the beta-lactamases and Carbapenemases. The pathogen has become a threat to both patients and healthcare providers as its incidence is on the increase, becoming a major global healthcare issue. The study was aimed at characterizing and determining the plasmid profile of resistant Klebsiella pneumoniae isolates from urinary tract of patients at Dalhatu Araf Specialist Hospital Lafia, Nasarawa State, Nigeria. Early morning mid-stream urine samples were collected from patients with urinary tract infections between April and May, 2019 and Klebsiella pneumoniae characterized on the basis of its antibiotic resistance pattern, and the plasmid DNA profile determined. Thirty-eight strains of resistant Klebsiella pneumoniae were obtained of which 33 showed resistance to more than three antibiotics. About 51.1% of the isolates were resistant to Tetracycline, while the isolates were least resistant to Azithromycin and Cefotaxime (30.3%) respectively. Klebsiella pneumoniae isolates showed 32 different resistance patterns, 24 of the strains had the capacity to produce Extended Spectrum Beta-lactamases enzymes: CTX-M 24(72.7%), SHV 19(57.6%) and TEM 16(48.5%) respectively. All the resistant Klebsiella pneumoniae isolated had the same plasmid size of 48.5 kilobases and only 1 plasmid each though they all obtained a multiple antibiotic resistance (MAR) index > 0.2. The study concluded that Klebsiella pneumoniae harbours genes which confer antibiotic resistance on the isolates. The study exposes further the challenge of antibiotic resistance and need for concerted effort at stopping the challenge of drug resistance.Int. J. Appl. Sci. Biotechnol. Vol 8(1): 21-28